Prevalence of preterm deliveries in women living with Human Immunodeficiency Virus at Mankweng Hospital, Limpopo - Rikhotso, Glenrose (My University, 2023)
Objectives: To determine the prevalence of preterm deliveries amongst HIV-positive women, to describe the demographic characteristics of HIV-positive women delivering preterm babies and to determine the possible risk factors that may be associated with preterm delivery amongst HIV-positive women delivering in Mankweng hospital. Materials and Methods: A retrospective cross-sectional study was conducted at Mankweng hospital labour ward and neonatal unit over twelve months, from January 2019 to December 2019. The maternity register was used to identify patients’ medical records which were then retrieved and used for the study. Results: The prevalence of preterm delivery amongst HIV-positive women was found to be 34.1%. This was very high compared to the global prevalence. Maternal age was not associated with preterm delivery. Factors that were found to be significantly associated with preterm delivery in our setting are hypertension, fibroid uterus, urinary tract infection and chorioamnionitis. Conclusion: The prevalence of preterm delivery in our setting is very high. The risk factors that contribute to preterm delivery among HIV-positive women are like that of the general population. Further studies need to be done to determine if these factors are increased among HIV-positive women.
Thesis (M.MED. (Paediatrics and Child Health)) -- University of Limpopo, 2023
Keywords: Prevalence; Preterm delivery; Human Immunodeficiency Virus; Risk factors; Delivery (Obstetrics); Pregnant women; Childbirth -- South Africa -- Limpopo; HIV-positive women -- South Africa -- Limpopo